2009
DOI: 10.1021/jf802960f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure of Selected Tuber and Root Starches and Effect of Amylopectin Structure on Their Physical Properties

Abstract: The objectives of this study were to characterize starches isolated from potato, canna, fern, and kudzu, grown in Hangzhou, China, for potential food and nonfood applications and to gain understandings of the structures and properties of tuber and root starches. Potato and canna starches with B-type X-ray patterns had larger proportions of amylopectin (AP) long branch chains (DP g37) than did fern (C-type) and kudzu (CA-type) starches. The analysis of Naegeli dextrins suggested that fern and kudzu starches had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 29 publications
5
41
1
Order By: Relevance
“…In contrast, Shinchunmi AP had 28.1% short chains (DP6‐12). Although Juhwangmi and Shinchunmi showed A‐types and Shinjami, Yeonwhangmi, and Jeungmi showed C‐types, the percentages of short chains (DP6‐12) and long chains (DP ≥ 37) differed from the Yoo et al results. Starches with a higher proportion of shorter AP chains (around DP10) showed slower retrogradation, whereas starches with a higher proportion of longer chains (around DP15) show faster retrogradation.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…In contrast, Shinchunmi AP had 28.1% short chains (DP6‐12). Although Juhwangmi and Shinchunmi showed A‐types and Shinjami, Yeonwhangmi, and Jeungmi showed C‐types, the percentages of short chains (DP6‐12) and long chains (DP ≥ 37) differed from the Yoo et al results. Starches with a higher proportion of shorter AP chains (around DP10) showed slower retrogradation, whereas starches with a higher proportion of longer chains (around DP15) show faster retrogradation.…”
Section: Resultsmentioning
confidence: 59%
“…The branch chain length distributions of AP are summarized in Table . Apart from other tuber and root starches , all APs except Shinchunmi AP showed the peak at DP12. Juhwangmi AP had the highest of 33.2% short chains (DP6‐12), and the average number and average weight of DP were of the lowest values, 13.7 and 16.1, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The C‐type starch pattern is a mixture of A‐ and B‐types owing to the presence of both A‐ and B‐polymorph crystallites and is considered to be more complicated . Amylopectin in C‐type starch granules has relatively intermediate chain lengths and both short and long chains …”
Section: Crystalline Characterization Of C‐type Starchmentioning
confidence: 99%
“…It can be seen that potato starch had the higher proportion of intermediate/short chains (DP 13‐24) and Alstroemeria starch had the higher proportion of long chains (DP ≥ 37). Yoo et al studied the effect of chain length distribution on swelling and pasting behavior of six native tuber and root starches. They found that high‐ M w AP molecules increased swelling (see Table ) as can be seen for Alstroemeria .…”
Section: Resultsmentioning
confidence: 99%